18 F-FLT-PET for response evaluation of MEK inhibitor selumetinib (AZD6244, ARRY-142886) in patients with solid tumors - Ingrid Desar; Rozemarie Gilles; Carla van Herpen; Anja J. Timmer-Bonte; Mireille Cantarini; Winette van der Graaf; Wim Oyen (World Journal of Nuclear Medicine)
Selumetinib (AZD6244, ARRY-142886) is a potent, selective, uncompetitive inhibitor of MEK 1 / 2, part of the RAF/MEK/ERK protein kinase signal cascade, which is responsible for tumor. This pilot study was used to explore if 18  F-fluoro-l-thymidine (FLT), a thymidine analogue positron emission tomography (PET) tracer and a surrogate marker for proliferation, can be used as an early predictor of response for patients with solid cancers treated with Selumetinib. FLT-PET scans were performed in four patients at baseline and after 2 weeks of treatment with Selumetinib. FLT uptake in tumors was analyzed qualitatively and quantitatively by measuring standard uptake value (SUV) max in regions of interest (ROI). Results were compared to computed tomography (CT) scans (baseline and after 8 weeks), which were evaluated using the response evaluation criteria in solid tumors (RECIST) 1.0 criteria. One patient with melanoma showed both a qualitative and quantitative decrease in FLT uptake associated with a decrease in sum of longest diameter of 12% RECIST on CT evaluation. Another patient who had colorectal carcinoma (CRC) showed a significant increase in FLT uptake with initially stable, but eventually progressive disease on CT. The other two patients (one with melanoma and one with CRC) showed no significant changes in FLT uptake, whereas CT evaluation showed progressive disease. This is the first report describing changes in FLT-PET in patients receiving Selumetinib. In two patients, changes in FLT uptake as early as after 2 weeks of treatment were consistent with CT results after 8 weeks. Biomarkers to predict and evaluate treatment the outcome of targeted therapies are highly warranted. These initial results need further investigation.